Analisis Minat Belajar Siswa Menggunakan Pendekatan Culturally Responsive Teaching pada Kelas V UPTD SDN Pamorah - Nur Aida; Andika Adinanda Siswoyo (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aims to describe the learning interest of fifth-grade students at UPTD SDN Pamorah after the implementation of the Culturally Responsive Teaching (CRT) approach in science learning. The study was motivated by students’ limited attention and participation, as classroom activities were not yet fully connected to their cultural backgrounds and experiences. A quantitative descriptive method was applied using a survey technique. The sample consisted of 37 students who completed a 30-item Likert-scale questionnaire. Data were analyzed using percentage calculations across four indicators: enjoyment, attention, curiosity, and engagement. The results indicate that students’ overall learning interest was at a moderate level, averaging 70.42%. The curiosity indicator achieved the highest score (85.88%), while attention was the lowest (60.73%). These findings suggest that the CRT approach effectively enhances students’ learning interest, particularly their curiosity, though further efforts are needed to strengthen their focus and active participation in class